Sheep and Cattle Reservoirs in the Highest Human Fascioliasis Hyperendemic Area: Experimental Transmission Capacity, Field Epidemiology, and Control Within a One Health Initiative in Bolivia - Mas-Coma, Santiago; Buchon, Paola; Funatsu, Ilra R.; Angles, Rene; Artigas, Patricio; Valero, M. Adela; Bargues, M. Dolores (Frontiers in Veterinary Science, 2020)
The Northern Bolivian Altiplano is the human fascioliasis hyperendemic area where the highest prevalences and intensities of infection by Fasciola hepatica in humans have been reported. Four animal species are the reservoir species in this area, namely sheep, cattle, pigs and donkeys. Livestock for the Aymara inhabitants is crucial because vegetable cultures are not viable due to the inhospitality of the very high altitude of 3820-4100 m. A One Health initiative has been implemented in this area in recent years, as the first such control action in a human endemic area ever. Among the different control axes included, special focus is devoted to the two main reservoirs sheep and cattle. Egg embryonation, miracidial infectivity, intramolluscan development, cercarial production, infected snail survival, and metacercarial infectivity were experimentally studied for each altiplanic sheep and cattle isolates. These laboratory studies were performed using altiplanic isolates of the lymnaeid species Galba truncatula, the only vector present in the hyperendemic area. Experiments were made at 12h day/ 12h night constant and varying photoperiods of 20º C/20º C and 22º C/5º C, and infections were implemented using mono-, bi- and trimiracidial doses. Results demonstrate that sheep and cattle have the capacity to assure fascioliasis transmission at very high altitude. Field surveys included prevalence studies by coprology on faecal samples from 1202 sheep and 2690 cattle collected from different zones of the Northern Bolivian Altiplano. Prevalences were pronouncedly higher and more homogeneous in sheep (63.1%; range: 38.9-68.5%) than in cattle (20.6%; range: 8.2-43.3%) in each one of the different zones. Although similarities between the prevalences in sheep and cattle appeared in the zones of the highest and lowest infection rates, this disappeared in the other zones due to cattle treatments. Comparison with past surveys demonstrate that this hyperendemic area is stable from the disease transmission point of view. Sheep and cattle should be therefore considered priority within the One Health action. Studies performed in the Bolivian Altiplano furnish a baseline for future initiatives to assess the transmission and epidemiological characteristics of fascioliasis in the way for its control in other high altitude Andean endemic areas.